Risk analysis and safety measures: JSA, HIRA, and FTA in LPG distribution - Dewantari, Nustin Merdiana; Ferdiansyah, Muhamad; Herlina, Lely; Mariawati, Ade Sri; Umyati, Ani (Journal Industrial Servicess, 2023)
Industrial competition is intensifying, raising the importance of Occupational Safety and Health (OSH) practices. This study focuses on LPG distributor Fajar Sidiq Nurhidayah, a company specializing in 3 kg LPG cylinders. The lack of safety inductions and adequate Personal Protective Equipment (PPE) heightens the risk of workplace accidents, necessitating this research to mitigate such risks. Employing the Job Safety Analysis (JSA), Hazard Identification and Risk Assessment (HIRA), and Fault Tree Analysis (FTA) methods, potential hazards were identified. JSA revealed risks like collisions, being struck by the truck's back, tube pinching, and ergonomic hazards, foreseeing injuries ranging from bruises to fractures and Musculoskeletal Disorders (MSDs). HIRA uncovered six hazards: one low-risk, four medium-risk, and one high-risk. FTA pinpointed the primary danger source to be the warehouse station due to operator negligence during tube lifting, lack of PPE usage, and entangled tubes, emphasizing the worker's condition and work environment.